2000
DOI: 10.1257/aer.90.5.1160
|View full text |Cite
|
Sign up to set email alerts
|

Does Schooling Cause Growth?

Abstract: A number of economists find that growth and schooling are highly correlated across countries. A model is examined in which the ability to build on the human capital of one's elders plays an important role in linking growth to schooling. The model is calibrated to quantify the strength of the effect of schooling on growth by using evidence from the labor literature on Mincerian returns to education. The upshot is that the impact of schooling on growth explains less than one-third of the empirical cross-country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
904
2
27

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,290 publications
(1,002 citation statements)
references
References 34 publications
44
904
2
27
Order By: Relevance
“…The range. Bils and Klenow (2000) found an average salary gain associated to an additional year of education of 9.5 per cent, and a range between 5 and 15 per cent for 36 out of 48 countries in their sample.…”
Section: Returns To Schoolingmentioning
confidence: 91%
See 1 more Smart Citation
“…The range. Bils and Klenow (2000) found an average salary gain associated to an additional year of education of 9.5 per cent, and a range between 5 and 15 per cent for 36 out of 48 countries in their sample.…”
Section: Returns To Schoolingmentioning
confidence: 91%
“…The human capital employed to produce output is introduced in the model following the formulation suggested by Bils and Klenow (2000), and is given by…”
Section: The Growth Model and Entrepreneurshipmentioning
confidence: 99%
“…However, overcoming this problem is not easy because finding a valid instrumental variable (IV) is almost impossible in the cross-country growth works. The reason for this is that growth theories are 4 Using the school enrolment rate as a proxy for the saving rate of human capital is problematic in the literature and leads researchers to employ average years of schooling as more reliable variables for human capital (see, for instance Bils and Klenow (2000), amongst others). We, however, employ the secondary school enrolment rate in order to follow the theoretical framework suggested by Mankiw et al (1992) more strictly as years of schooling are a stock rather than a flow variable for human capital.…”
Section: Economic Growth and Openness To International Trade: Baselinmentioning
confidence: 99%
“…Barro (1991) found that "poor countries tend to catch up with rich countries if the poor countries have high human capital per person (in relation to their level of per capita GDP)". Benhabib and Spiegel (1994), Bils and Klenow (2000) and Prichett (2001) find a weak relation between education quantity and economic growth.…”
Section: Literature Reviewmentioning
confidence: 95%